Transport and pinning properties of Ag-doped FeSe0.94. (13th January 2015) - Nazarova, E; Balchev, N; Nenkov, K; Buchkov, K; Kovacheva, D; Zahariev, A; Fuchs, G
Abstract: We investigated the superconducting transition and the pinning properties of undoped and Ag-doped FeSe0.94 at magnetic fields up to 14 T. We established that, due to Ag addition, the hexagonal phase formation in melted FeSe0.94 samples is suppressed and the grain connectivity is strongly improved. The obtained superconducting zero-field transition becomes sharp, with a transition width below 1 K. Tc and the upper critical field were found to increase, while the normal-state resistivity was significantly reduced, becoming comparable with that of FeSe single crystals. In addition, a considerable magnetoresistance was observed due to Ag doping. The resistive transition of undoped and Ag-doped FeSe0.94 is dominated by a thermally activated flux flow. From the activation energy U versus H dependence, we found a crossover from single-vortex pinning to a collective-creep pinning behavior by increasing the magnetic field.